EFFICACY OF SGLT-2 INHIBITORS IN THE TREATMENT OF TYPE 2 DIABETES: SINGLE CENTRE EXPERIENCE - Ramazan Çakmak; Golpouneh Alizad Oghyanous; Özlem Soyluk Selçukbiricik; Kubilay Karşıdağ (İstanbul Tıp Fakültesi Dergisi)
Objective: Sodium-glucose transporter-2 (SGLT-2) inhibitors lower blood glucose levels by reducing renal glucose reabsorption without affecting insulin secretion. The aim of our study was to evaluate the effect of SGLT-2 inhibitor treatment on glycemic control and the possible superiority of the drugs by comparing clinical parameters and laboratory findings in Type 2 diabetes mellitus (T2DM) patients. Material and Methods: Two hundred and nineteen T2DM patients who received SGLT-2 inhibitor therapy [empagliflozin (EMPA) (n=146) or dapagliflozin (DAPA) (n=73)/10 mg] were enrolled retrospectively. The patients’ demographic characteristics, detailed medical history, comorbidities, physical examination findings, complications, weight and systolic-diastolic blood pressure follow-up, laboratory findings (at baseline, 3rd, and 12th month), and overall follow-up outcomes were evaluated. Result: The mean values of HbA1c and fasting blood glucose (FBG) decreased significantly compared with the baseline values after the treatment. The mean body weight and uric acid values were significantly reduced in the 3rd month of the treatment. Similarly, the values of the liver function tests decreased substantially after treatment. Conclusion: The beneficial effects of SGLT-2 inhibitors on glycemic control and liver functions in patients with T2DM have been demonstrated. In addition, there was no major difference in terms of clinical parameters, laboratory findings, and drug safety in patients between EMPA and DAPA.